The Third International Science and Practice Conference "Tengriism and epic heritage of Eurasian people: origins and modernity” - Fedorova, Lena V. (The New Research of Tuva, 2011)
Article presents a review of 3 international conferences devoted to the problem of Tengriism of Eurasian people denoting advantages of the third one, held in Kyzyl (Tuva) in July 2011.